Titanium-based nanoparticles: innovations in energy applications, wastewater treatment, and tissue engineering for cardiac regeneration - Ikhazuagbe H. Ifijen; Uchenna Uzoma Akobundu; Janefrances U. Chukwu; Stella Eberechi Obuba; Sifon Enefiok Edem; Ebuloku Chijindu Solomon; Daniel Aluah; Adeleke Damilola Adekola; Onuh Emmanuel Edoka; Emmanuel Ikechukwu Okeke (Discover Chemistry)
Abstract Titanium-based nanoparticles (TiNPs) show considerable promise in energy, environmental, and biomedical applications. This study highlights their roles in photovoltaics, hydrogen production, wastewater treatment, and cardiac tissue engineering, offering quantitative insights into performance improvements and associated challenges. In energy systems, titanium dioxide (TiO₂) has enhanced dye-sensitized solar cells (DSSCs) with up to 25% increased light absorption and 30% improved charge separation, while Ti-based nitrides and carbides show a 20% boost in charge transport efficiency. TiNPs also demonstrate up to a 40% improvement in hydrogen evolution rate for photocatalytic hydrogen production. In environmental remediation, TiNPs achieve over 95% pollutant removal through advanced oxidation, though scalability issues like catalyst recovery and stability remain a challenge. In cardiac tissue engineering, TiNP-based scaffolds face limitations due to rigidity, low electrical conductivity, and biocompatibility concerns. Addressing these issues requires hybrid materials and advanced fabrication techniques such as 3D printing and electrospinning. Future research should focus on optimizing TiNP properties, overcoming scalability, mechanical, and biocompatibility barriers, and advancing TiNP applications in renewable energy, environmental sustainability, and regenerative medicine.